2022
DOI: 10.3991/ijet.v17i20.31421
|View full text |Cite
|
Sign up to set email alerts
|

University English Language Teachers’ Use of Digital Platforms for Online Teaching

Abstract: Digital disruptions have affected higher learning institutions and forced educators across the globe to use digital platforms for online teaching. This paper presents the findings of a pilot study that investigated (1) the usage of digital platforms for teaching English at a Malaysian university and (2) how university English language teachers employed digital platforms for online teaching. An online questionnaire survey was completed by 19 university English teachers who volunteered to take part. Cross-tabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Also, this research showed that SI had a significant positive relationship with BI, which was consistent with the findings of [3]. These findings also agree with the study by [11] about factors affecting the adoption of technologies, where the results showed that SI had a significant relationship with BI.…”
supporting
confidence: 91%
“…Also, this research showed that SI had a significant positive relationship with BI, which was consistent with the findings of [3]. These findings also agree with the study by [11] about factors affecting the adoption of technologies, where the results showed that SI had a significant relationship with BI.…”
supporting
confidence: 91%
“…Aspects of students' use of digital platforms were identified using a questionnaire distributed to all participants with open-ended and multiple choice question types with a 5-point Likert type scale and it had 30 items. the components of questionnaire adapted from (Amin & Paiman, 2022) The questionnaire was tested for reliability and validity with a Cronbach α value of 0.73 (Gülbahar, 2012). While the satisfaction aspect was identified using the level of satisfaction in the online learning environment using a questionnaire distributed to all participants with open-ended and multiple-choice question types with a 5-point Likert type scale.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars showed that the sudden shift to online delivery did not give sufficient time for educators to re-examine traditional activities before they moved online (Li et al 2021). Furthermore, according to recent investigations, virtual classes were characterised by more superficial interactions (Alwaheebi and Al-Qahtani 2022), and internet accessibility was an issue for many students in several countries (Nkemleke 2021;Mohamed Amin and Paiman 2022).…”
Section: Online Teaching and Emergency Online Teaching In Higher Educ...mentioning
confidence: 99%